Factors Affecting to the Implementation of Disease Prevention and Control By Health Network in Had Arsa Sub-district, Sapphaya District, Chai Nat Province - ผาสุข จุฑารัตน์; อิ่มสมบูรณ์ ธนวรรธน์ (Disease Control Journal, 2012)
The objective of this qualitative study was to identify the factors affecting to the implementation of disease prevention and control by health networks in Had Arsa Sub-district, Sappaya District, Chai Nat Province. The sample groups included governmental network, business network, social network and nongovernmentorganization network. The questionnaire concerned on network opinions on the factors influencing the implementation of disease prevention and control by the health networks in this sub-district. The study revealed that the first factor was participation of their colleagues in the beginnings and involve allprocess of implementation continuously. The second factor was to achieve the same goals, creating the same perception and mindset among the colleagues in the network. The positive interaction was used for active motivation, example; the chief of local authority who demonstrated to encourage working people in the communities by setting activities such as knowledge exchange and rewards etc. In addition, resources and support were also important factors affecting to the success implementa- tion of health networks of Had Arsa Sub-district.